Is clicking mechanism good for flapping wing micro aerial vehicle? - Chin, Yao Wei (2014)
In this paper, we examine the effect of non-sinusoidal flapping motion caused by click mechanism and compared it to a sinusoidal flapping motion. Many had observed and described the click mechanism through insect’s anatomy. Through theoretical models and numerical studies, some dismissed its effect on flapping efficiency, while others predicted better thrust generation with it. Without concrete experimental proof, the argument is hypothetical. This work showed the benefits of the click mechanism by experiment, with its simple compliant thorax designed using carbon fiber and polyimide film. The click mechanism system is designed like a thin elastic plate which was compressed until bent, with its center point stable at either the top most extreme or the bottom most extreme positions. ‘Clicking’ occurs when the plate center is moved forcibly from one extreme to the other. Before it passes the midpoint, the plate center moves slowly as it tends to return to the original extreme and resist the displacement. When moved passed the midpoint, it now tends to move to the other extreme, together with the external force, resulting in a fast, snapping ‘click’ to the other extreme. Hence, the clicking prototype showed a sudden high increase in wing flap speed when it is moved beyond midpoint towards the other end. It also showed quick wing reversal and is able to produce consistent large wing stroke (~115°). The clicking prototype, which weighs 3.78g, produces a higher thrust of 2.9g at a flapping frequency of 19Hz. In comparison, a 3.26g prototype of sinusoidal flapping motion with similar design configuration produces only 2.2g of thrust at 19Hz.